(untitled) (Global Journal of Science Frontier Research, 2023)
The recently discovered topological theory of quantum gravity TTQG is projected as a multi block theory having a core central block with multiple sub blocks grafted on the central block Emerged out from the said central block the sub blocks are spread all around multiple corners and they are connecting TTQG to most of the principal theories of physics and cosmology While all the new concepts of TTQG are embedded in the core central block the sub blocks truly play the role of compatibilizer In this article it has been shown straight forward that each and every sub block is compatibilizing one or the other streams like e g quantum mechanics the relativity theories thermo-dynamics cosmology quantum computing etc and the others Also an altogether new spatial and topological interpretation of Quantum mechanics have been given in regard to the operability of quantum mechanical operators on the wave function The most of the principal theories of physics and cosmology are non topological and suffer from the serious problem of formlessness or shapelessness of the physical variables of the universe In this research article it has been demonstrated that the TTQG apart from its compatibilizer action on the other theories of physical science also acts as a modifier of the said theories through its following inherent broad frame logic and philosophies 1 The building blocks of the universe are the push forward and the pull back gravitons and those are originated from the singularity gravitons 2 The phenomenon of gravitation is the superposition of space inversion fields and the said superposition gives birth to the singularity gravitons 3 The physical variables time pull back graviton and temperature push forward gravitons are entangled to each other in the multiplicative inverse sense 4 The exchange of forces or the interactions among the gravitons in the universe occur through the well defined quanta 5 Entropy is a energy E time t interfering or hybrid concept and the Et hybrid governs the 3 different laws of thermodynamics 6 The parameter of quantum physics the Planck s constant h is basically the same as the thermodynamic parameter S degree of randomness or entropy 7 The Heisenberg s uncertainty principle is converging to the 2nd law of thermodynamics although the said laws have been presented in two entirely different ways 8 The proper understanding of the phenomena of the mass wave duality is made through the TTQG depicted universal graviton cycle and black body radiation 9 The Qubits or the Quantum bits of Quantum computing are the entangled color gravitons of TTQG derived new theory of color physics 10 The result of superposition interference and entanglement of order and mass gravitons are the gravitational waves 11 The dimensionality of the universe is derived through the unification horizon of quantum mechanics and quantum gravity